Prevalence and Protective Factors Against Depression among Adolescents in Three Southern Border Provinces of Thailand - Tohpaeroh, Muslin; Saetung, Benjawan; Jehloh, Latifah; Sawan, Sarinee (Jurnal Keperawatan Soedirman, 2025)
Depression in adolescents is a significant public health issue because adolescents are the age group that most often engage in self-harm. Thus, it is crucial to study the protective factors against depression that integrate internal and external factors. This study aimed to determine the prevalence and examine the protective factors against depression among adolescents in southern Thailand. This study used a descriptive-predictive research design. A total of 440 high school students served as the study's samples. They were selected using purposive sampling techniques with a multistage sampling procedure. Data were analyzed using ordered logistic regression analysis. The results showed that 66.4% of the sample had depression, with most of the students having mild depression at 46.8%. Seven protective factors were found to prevent depression in adolescents. Adolescents who have healthy family relationships and moderate spiritual well-being, in terms of existential well-being, were 16.28 and 0.73 times less likely to have depression, respectively. Meanwhile, adolescents with low levels of psychological immunity in optimism, low and moderate levels of apperception, lack of belief in the power of wisdom and low support from the community, and low and moderate levels of spiritual and religious well-being were more likely to have depression.